Second-line treatment strategies of ulcerative colitis after conventional therapy failure: A systematic review and network meta-analysis of randomized controlled trials - Yanan Xu; Wenshuo Jiang; Meizhu Jiang; Bin Zhu; Jiping Huo; Mingfen Wu; Li Yang (PLoS ONE, 2025)
Purpose This study aimed to compare the efficacy and safety of pharmacotherapies for ulcerative colitis (UC), promoting more precise management of refractory ulcerative colitis. Methods Relevant randomized controlled trials involving refractory UC patients were systematically searched in electronic databases, including MEDLINE, EMBASE, and the Cochrane Library. Data were independently extracted by three investigators. Risk ratios (RRs) with 95% confidence intervals (CI) were calculated for key outcomes: remission, response, mucosal healing, and serious adverse events using random-effects models. Network meta-analysis, utilizing a frequency model, established comparative rankings, with surface under cumulative ranking curve (SUCRA) determining optimal treatments. Results A total of nineteen studies, containing 5,450 patients, were included. In the induction phase, Qing-Chang-Hua-Shi emerged as the most effective drug for remission (RR vs placebo 0.78, 95% CI 0.64–0.95; SUCRA, 0.89). Cyclosporine showed the most promising effect for treatment response (RR 0.22, 95% CI 0.07–0.67; SUCRA, 0.90). Tacrolimus was most effective in terms of mucosal healing (RR 0.57, 95% CI 0.44–0.73; SUCRA, 0.89). Recombinant interferon-β-1a exhibited the lowest risk of serious adverse events (RR 0.08, 95% CI 0.01–0.62; SUCRA, 0.94). Conclusion No single drug demonstrated consistent superiority across all four evaluated outcomes for refractory ulcerative colitis. Treatment strategies should therefore be individualized according to specific clinical objectives and the quality of available evidence.